Menuju Cita Supremasi Hukum - Khumarga, Dahnial (Pelita Harapan University, 2003)
Supremacy of Law, which means that all persons (individuals and government) are subject to laws. Supremacy of the law requires the rule of law. Aristoteles said more than two thousand years ago: